1970
DOI: 10.1111/j.1745-4603.1970.tb00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Different Foods in the Standard Shear Compression Cell of the Shear Press and the Effect of Sample Weight on Peak Area and Maximum Force

Abstract: Twenty-four foods (encompassing fruits, vegetables, meat, bread, cheese and rice) were tested in the Allo Kramer Shear Press at various weight levels ranging from those needed to cover the bottom of the cell to those required for a complete fill. The relationship between maximum force values and sample weight was found to be different for different foods. Products could be grouped into three general categories: those exhibiting a constant force to weight ratio (e.g. white bread, sponge cake), those exhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1972
1972
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…The maximum force (N) at low (20%) and high (80%) deformation and the work until the maximum force were calculated. All of these parameters were divided by the weight of the sample (Szczesniak et al, 1970).…”
Section: Muscle Histological Analysismentioning
confidence: 99%
“…The maximum force (N) at low (20%) and high (80%) deformation and the work until the maximum force were calculated. All of these parameters were divided by the weight of the sample (Szczesniak et al, 1970).…”
Section: Muscle Histological Analysismentioning
confidence: 99%
“…Because of the nondisintegrating characteristic of the testas, stress during the compression and resistance at the slot would result in the observed higher maximum force. Compression, shear, and extrusion are important forces operating in a shear cell, and evaluation of mathematical models concerning one (compression or shear), two, or three forces revealed that extrusion in combination with compression or shear, or compression plus shear, were appropriate models for explaining the behavior of 21 out of 24 tested foods (Szczesniak et al 1970). The different textures of testas and embryos might yield forces caused by different combinations of basic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Annonaceae, pineapple). It has been reported (Szczesniak et al 1970) that parameters measured by instruments such as the Shear Press depend on the sample size even when the numerical values are adjusted to a unit sample weight. The nature of the dependency itself has been found to be characteristic of the fruit type.…”
Section: Discussionmentioning
confidence: 99%